Literary Types of Epic Genres and their Analysis (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In this article, various genres of artistic works, important aspects of the period are analyzed in depth, and the ideas and problems that attract the attention of many people are analyzed.